Inhibition of Microglial Activation Protects Hippocampal Neurogenesis and Improves Cognitive Deficits in a Transgenic Mouse Model for Alzheimer's Disease - Biscaro, Barbara (Neurodegener Dis, 2012)
BACKGROUND: Activated microglia with macrophage-like functions invade and surround β-amyloid (Aβ) plaques in Alzheimer's disease (AD), possibly contributing to the turnover of Aβ, but they can also secrete proinflammatory factors that may be involved in the pathogenesis of AD. Microglia are known to modulate adult hippocampal neurogenesis. OBJECTIVES/METHODS: To determine the role of microglia on neurogenesis in brains with Aβ pathology, we inhibited microglial activation with the tetracycline derivative minocycline in doubly transgenic mice expressing mutant human amyloid precursor protein (APP) and mutant human presenilin-1 (PS1). RESULTS: Minocycline increased the survival of new dentate granule cells in APP/PS1 mice indicated by more BrdU+/NeuN+ cells as compared to vehicle-treated transgenic littermates, accompanied by improved behavioral performance in a hippocampus-dependent learning task. Both brain levels of Aβ and Aβ-related morphological deficits in the new neurons labeled with GFP-expressing retrovirus were unaffected in minocycline-treated mice. CONCLUSIONS: These results suggest a role for microglia in Aβ-related functional deficits and in suppressing the survival of new neurons, and show that modulation of microglial function with minocycline can protect hippocampal neurogenesis in the presence of Aβ pathology.